Instability of Romania's fruit production and the responsible factors for this phenomenon - Viorică Gavrila (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The paper offers a framework of understanding the stability/instability degree of the fruit domain's production system both at national and regional profile. We chose the utilization of Cuddy Della Valle variability index. We followed the evolution of the variability index for two different periods, respectively: 1996-2005 (P1) and the period 2006-2015 (P2). Reducing the variability index through the time is confirming the hypothesis that in case of ruit trees' orchards in our country the production's stability is greatly affected by the structural factors.
Keywords: Q 11; 330; production; fruits; instability